An overview of the Syrphidae (Diptera) of Saudi Arabia - Dawah, Hassan A.; Abdullah, Mohammed A.; Ahmad, Syed Kamran; Al-Dhafer, Hathal; Turner, James (Zootaxa, 2020)
Despite the species richness of hoverflies (Diptera: Syrphidae) world-wide (about 6,200 species) and their role as agents for controlling plant pests, their significance as pollinators, and as bioindicators of site quality, hoverfly fauna of Saudi Arabia is poorly known. In exploring the biodiversity of Diptera in southwest Saudi Arabia a survey of the hoverfly fauna of Jazan, Asir, Najran and Al-Baha was performed mainly using Malaise traps, sweep nets and light traps from 2011 to 2014. Forty known species of Syrphidae were identified and recorded in this study, 19 of them new to Saudi Arabia. This makes the total number of Syrphidae species recorded in Saudi Arabia (including one species recorded by others) is 41. In addition, three taxa belonging to the genera Eumerus Meigen, Orthonevra Macquart, and Paragus Latreille that could not be identified safely to species level because there were no adequate identification keys or males were missing in the collected material. A key to the genera of Syrphidae occurring in Saudi Arabia is provided. The fauna of Syrphidae recorded in this study consists much more of Afrotropical zoogeographical elements than Palaearctic ones. A complete checklist of Syrphidae of Saudi Arabia is provided. Biological data, where known, and world-wide distribution of the studied taxa are provided. This paper is published with the purpose of assisting biogeographical, biological or ecological studies on syrphids in Saudi Arabia.